Impact of Chronic Antiplatelet Therapy on Infarct Size and Bleeding in Patients With Acute Myocardial Infarction. (September 2018) - Campodonico, Jeness; Cosentino, Nicola; Milazzo, Valentina; Rubino, Mara; De Metrio, Monica; Marana, Ivana; Moltrasio, Marco; Grazi, Marco; Lauri, Gianfranco; Bonomi, Alice; Veglia, Fabrizio; Chiorino, Elisa; et al.
Background: Patients hospitalized with acute myocardial infarction (AMI) are often on prior single antiplatelet therapy (SAPT) or a dual antiplatelet therapy (DAPT). Whether chronic SAPT or DAPT is beneficial or associated with an increased risk in AMI is still controversial. Methods and Results: We prospectively enrolled 1718 consecutive patients with AMI (798 ST-segment elevation myocardial infarction and 920 non-ST-segment elevation myocardial infarction) who were divided according to their chronic APT (no APT, SAPT, or DAPT). The study primary end point was the infarct size, as estimated by troponin I peak. Incidence of major bleeding was also evaluated. Five hundred thirty-six (31%) patients were on chronic SAPT and 215 (13%) on DAPT. A graded increase in Global Registry of Acute Coronary Events (GRACE) and Can Rapid risk stratification of Unstable angina patients Suppress ADverse outcomes with Early implementation of the ACC/AHA guidelines (CRUSADE) risk scores was found going from patients without APT to those with DAPT, while a progressive smaller troponin I peak was observed with the increasing number of chronic antiplatelet agents (11.2 [interquartile range: 2-45] ng/mL, 6.6 [1-33] ng/mL, and 4.1 [1-24] ng/mL; P < .001 for trend). This result was maintained after adjustment for baseline ischemic risk profile (GRACE score) and other major confounders ( P < .001). The incidence of bleeding was higher in patients on chronic APT than in those without APT (5.2% vs 2.4%; P = .002). However, when the bleeding risk was adjusted for the CRUSADE risk score, chronic SAPT (odds ratio [OR]: 1.40, 95% confidence interval [CI]: 0.77-2.53) and DAPT (OR: 0.70, 95% CI: 0.29-1.70) were not associated with an increased bleeding risk. Conclusion: In patients with AMI, chronic APT is associated with higher baseline ischemic and bleeding risks. Despite this and unexpectedly, they have a smaller infarct size and similar adjusted bleeding risk.